Characterization of the aurantimycin biosynthetic gene cluster and enhancing its production by manipulating two pathway-specific activators in Streptomyces aurantiacus JA 4570. Issue 1 (December 2016) - Zhao, Houyuan; Wang, Liang; Wan, Dan; Qi, Jianzhao; Gong, Rong; Deng, Zixin; Chen, Wenqing
Abstract Background Aurantimycin (ATM), produced byStreptomyces aurantiacus JA 4570, is a potent antimicrobial and antitumor antibiotic. Although the chemical structure of ATM is highly distinctive and features a cyclohexadepsipeptide scaffold attached with a C14 acyl side chain, little is known about its biosynthetic pathway and regulatory mechanism. Results In this work, we report the identification and characterization of the ATM biosynthetic gene cluster fromS. aurantiacus JA 4570. Targeted inactivation ofartG, coding for a NRPS enzyme, completely abolished ATM production, thereof demonstrating the target gene cluster (art ) is responsible for ATM biosynthesis. Moreover, four NRPS adenylation (A) domains including a freestanding enzyme ArtC have been characterized in vitro, whose substrate specificities are consistent with in silico analysis. Further genetic analysis of the two regulatory genesartB andartX unambiguously suggested both of them play positive roles in ATM biosynthesis, and ATM-A production was thus rationally enhanced to about 2.5 fold via tandem overexpression ofartB andartX inS. aurantiacus JA 4570. Conclusions These results will provide the basis for the understanding of precise mechanisms for ATM biosynthesis, and open the way for both rational construction of high-production ATM producer and orient-directed generation of designer ATM derivatives via synthetic biology strategies.